Post-Menopausal Symptoms: Do They Affect A Woman’s Quality Of Life? - Maqsood, Zainab; Noreen, Humera; Ejaz, Lubna; Bilqis, Humaira; Shaista; Arooj, Amara (Journal of Rawalpindi Medical College, 2025)
Objective: Menopause is a physiological event and transition of life in all women at the age of 45. Assessment of Quality of life (QoL) at menopause has been largely inadequate. The study aims to assess the Quality of life in post-menopausal women of Pakistan Methods: An Analytical cross-sectional study was conducted in the gynaecology/obs unit of Holy Family Hospital, after taking approval from the ethical review board. 580 women were included in the study. Data collection was facilitated through a questionnaire, administered by the gynaecology OPD duty doctor after conducting interviews with the postmenopausal women. The questionnaire was adopted from the Menopause Rating Scale (MRS) and the World Health Organisation Quality of Life (WHOQoL) proforma. Results: Mean age at menopause was 49.9 years. Postmenopausal symptoms were experienced by 95% of women of varying severity, with the most commonly reported symptoms being hot flushes (79%), followed by palpitation (70%), depressive illness (45%), sexual problems/decreased libido 33% and urinary problems 25%. Around 16 per cent of women reported an effect on Quality of life due to menopausal symptoms. A positive correlation was found between QoL and the education of the patient. There was a negative correlation between QoL and parity and the age of the patient. In multiple regression analysis, vasomotor symptoms score (hot flashes and night sweats), psychological symptoms (depressive mood) and urogenital symptoms (sexual problem and bladder problem) remained as main predictive factors of QOL of postmenopausal women, accounting for 38% of variance (adjusted R2 =0.38). Conclusion: The experience of menopausal symptoms varies across cultures and regions, impacting women’s quality of life. Factors like symptom prevalence, parity, economic status, and cultural beliefs significantly shape the menopausal experience, highlighting the need for tailored support and interventions to improve women’s well-being during this phase of life.